(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract—AI is significantly impacting cardiovascular disease diagnosis and management, enhancing accuracy, speed, and early detection. AI algorithms can analyze ECGs, imaging data, and other clinical information to identify heart conditions, predict risks, and personalize treatment strategies. This includes detecting structural heart diseases like hypertrophic cardiomyopathy and aortic stenosis, as well as predicting long-term outcomes for heart failure patients.